Etnomatematika: Konsep Geometri Bangun Datar pada Permainan Tradisional Marsitekka dan Rumah Bolon - putri, risma aprilia; Sidabutar, Melani; Sinurat, Anggun; Pandiangan, Mesriana; Khairunnisa, Ilma; Perangin-angin, Rachel A.J. (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to explore the geometric concepts of two-dimensional shapes embedded in the traditional Marsitekka game and the architectural structure of Rumah Bolon as representations of ethnomathematics within the Batak Toba culture. The background of this research highlights the importance of contextual and meaningful mathematics learning through the integration of local cultural elements. The research employed a qualitative library research method, where data were collected through a literature review of scholarly journals, academic articles, and related documents. Content analysis was used to identify geometric forms found in the cultural objects under study. The results reveal that the Marsitekka game contains various two-dimensional shapes such as squares, rectangles, semicircles, and triangle variations visible in the game’s layout and the Gaco objects used. Meanwhile, Rumah Bolon features shapes such as isosceles triangles, trapezoids, circles, and rectangles apparent in the roof structure, building façade, and Gorga ornamentation. These findings reinforce that both cultural elements have significant potential as contextual learning media for teaching geometry, particularly two-dimensional shapes, through an ethnomathematical approach. This study is expected to serve as a foundation for developing teaching materials based on local wisdom to enhance students’ understanding and interest in mathematics.